Management of Clinical Supervision in Increasing Educator Competence at Madrasah Tsanawiyah Negeri 3 Langkat - Darno Darno; Fachruddin Azmi; Mardianto Mardianto; Fatimah Lubis (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study aims to reveal and analyze: 1) How is clinical supervision managed at Madrasah Tsanawiyah Negeri 3 Langkat? 2) What is the clinical supervision management model for improving the competence of teaching staff at Madrasah Tsanawiyah Negeri 3 Langkat? 3) What are the supporting and inhibiting factors for clinical supervision management in improving the competence of teaching staff at Madrasah Tsanawiyah Negeri 3 Langkat? This study employs a multisite qualitative method, with data collection techniques such as interviews, observation, and document studies, while the researcher refers to the data validity standard proposed by Lincoln and Guba, which consists of credibility, transferability, dependability, and comfirmability, to strengthen the validity of the data findings and the authenticity of the research. The results of this study indicate that: 1) The management of clinical supervision at Madrasah Tsanawiyah Negeri 3 Langkat can be concluded that the madrasa head, deputy head of madrasa, senior study teacher, and madrasa supervisor have carried out clinical supervision in various ways; (1) the Madrasah head, deputy madrasah head, senior subject teacher, and madrasah supervisor provide input or reinforcement related to the learning process; (2) The Madrasah head, deputy madrasah head, senior subject teacher, and madrasah supervisor plan and schedule clinical supervision of the teacher council, both those who volunteer to be supervised and those who do not volunteer; (3) Madrasah heads, vice principals, senior subject teachers, and madrasah supervisors motivate teachers to be even more enthusiastic about teaching; (4) The Madrasah head, vice principal, senior subject teacher, and madrasah supervisor provide input so that writing, reading and scientific publications should not be abandoned; (5) Madrasah heads, vice principals, senior subject teachers, and madrasah supervisors encourage teachers who are already good at teaching to keep them and not feel satisfied; (6) Madrasah heads, vice principals, senior subject teachers, and madrasa supervisors teach how to be professional teachers; (7) the Madrasah head, deputy madrasah head, senior subject teacher, and madrasa supervisor supervise clinically so that the administration and teaching materials are well prepared; (8) Madrasah heads, deputy madrasah heads, senior subject teachers, and madrasah supervisors supervise clinically so that they are active in teacher forums Consultations with subject teachers and teacher working groups; 2) Many activities are carried out under the clinical supervision management model to improve the competence of teaching staff at Madrasah Tsanawiyah Negeri 3 Langkat. These activities include visits classified into two types: individual clinical supervision and collective supervision. Individual clinical supervision includes class visits, teacher requests, individual communication, and a personal evaluation process for learning. Collective clinical supervision is carried out through teacher group work, workshops, committees, teacher meetings, learning demonstrations, field trips, lectures/studies, curriculum laboratories, and panel discussions; and 3) Factors supporting and impeding clinical supervision management in improving teaching staff competence at Madrasah Tsanawiyah Negeri 3 Langkat. Teachers on average master information and technology such as LCD, Infous, PPT, video, and learning media, as well as the availability of the internet and mosques. The teacher then provides administrative reports, the teachers want to adapt to technological developments, the madrasa head is able to create a comfortable working environment, and the madrasa head motivates, loves, cares for, guides, and fosters the teachers. Then there are time constraints, teachers who are not mentally prepared when supervision is held, teachers who do not understand clinical supervision, electricity that is not evenly distributed in class, teacher awareness to improve themselves, not yet able to collaborate, madrasa supervisors who do not provide guidance and guiding teachers, supervision that is not continuous for repairs, electronic facilities and infrastructure that are still inadequate.